Production of microcrystalline cellulose from palm cellulose pulp - Muhammad Arif Fahmi, Supian (2017)
Malaysia currently accounts for 39 % of world palm oil production and 44% of world exports. Being one of the biggest producers and exporters of palm oil and palm oil products, the palm oil production in Malaysia contributes 85.5% of the total biomass production in Malaysia. From the 85.5%, empty fruit bunches (EFB) are the most that contribute to biomass waste produced. Biomass is made up of cellulose, hemicellulose, and lignin. Thus, it has great potential for use as a cellulose source for the production of microcrystalline cellulose (MCC). Just like that, we can produce very valuable product from waste that are free. The study on the operable condition in synthetizing the microcrystalline cellulose (MCC) take place by understanding the effect of consistency and sodium hydroxide (NaOH) concentration in the alkaline pretreatment for the production of microcrystalline cellulose (MCC) from empty fruit bunch (EFB). The empty fruit bunch are pretreated using hot water that proceeded by with alkaline pretreatment using sodium hydroxide (NaOH) and lastly, the microcrystalline cellulose (MCC) were produced by using hydrolysis process using hydrochloric acid (HCL). The alkaline pretreatment was optimized by using different concentration of sodium hydroxide (NaOH) solution and the operable condition for the synthesis of microcrystalline cellulose (MCC) was determined by the consistency of the slurry solution. The total weight loss during the alkaline pretreatment produced was determined using a formula and the lignin content was determined by using TAPPI standard T-222 method. The properties of original fiber, treated fiber, alpha cellulose and microcrystalline cellulose (MCC) were determined by Fourier Transform Infrared (FTIR) Spectroscopy. Scanning Electron Microscope (SEM) analysis has shown clearly visible alteration before and after hydrolysis. The operable condition of for the synthesis of microcrystalline cellulose (MCC) is with the consistency of 5% and the optimal concentration for the alkaline pretreatment using sodium hydroxide (NaOH) solution is 20%. These optimization factors allowed the production microcrystalline cellulose (MCC) from the empty fruit bunch (EFB). Thus providing plenty of opportunities for its many applications.